1999
DOI: 10.1111/j.1525-1594.1999.06429.x
|View full text |Cite
|
Sign up to set email alerts
|

PEG‐Hemoglobin as a Resuscitation Solution in the Treatment of Hypovolemic Shock in the Anesthetized Rat

Abstract: This study was designed to determine the advantages of using the hemoglobin-based oxygen carrier, polyethylene glycol conjugated bovine hemoglobin (PEG-Hb), as an additive to Ringer's lactate solution (RLS) for the treatment of acute hemorrhage in anesthetized female rats. Different compositions of PEG-Hb and RLS were administered intravenously in a paradigm that provided 30 ml/kg of resuscitation fluid following an episode of 15 min of hypotension. Hypotension was achieved by the removal of blood (1 ml/min) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Consistent with this idea are findings with a second generation HBOC that has recently been developed (Winslow et al. 1998; Conover et al. 1999; Wettstein et al.…”
Section: Discussionsupporting
confidence: 57%
“…Consistent with this idea are findings with a second generation HBOC that has recently been developed (Winslow et al. 1998; Conover et al. 1999; Wettstein et al.…”
Section: Discussionsupporting
confidence: 57%
“…Data from clinical studies of polymerized human Hb report efficacy without hypertension in cases of acute trauma (8,17), but published data from preclinical studies are lacking. In contrast, the cumulative evidence with PEG-modified Hb (2,3,36,39) demonstrates the lack of hemodynamic actions in a number of animal models. The primary observation in the present study, i.e., lack of hypertension or rise in systemic vascular resistance, represents the first publication, to our knowledge, of this finding with PEG-modified Hb in a large-animal model of hemorrhage and resuscitation.…”
Section: Discussionmentioning
confidence: 73%
“…Earliest attempts to use purified Hb from RBCs demonstrated that it is unstable in vivo ; it dissociates into constituent chains and have significant toxic reactions upon administration (Savitsky et al, 1978; White et al, 1986; Chang, 1998; Chan et al, 2000). While the dissociation problems could be partially addressed by approaches such as cross linking (Creteur et al, 2000; Gould et al, 2002; Squires, 2002; Stowell, 2002) and/or its conjugation to poly(ethylene glycol) (Conover et al, 1999), oxidative degradation of Hb at body temperature remains an unsolved problem to date. Oxidation of Hb increases the rate of heme loss resulting in its denaturation.…”
Section: Discussionmentioning
confidence: 99%